Prevalence and risk factors of healthy lifestyle among 30 - 79 years old Yi ethnic residents in Chuxiong Yi Autonomous Prefecture, Yunnan province: a cross-sectional survey in 2019 - Su-su ZENG; Qiong MENG; Xue-hui ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the prevalence and risk factors of healthy lifestyle among Yi ethnic residents aged 30 to 79 years in Chuxiong Yi Autonomous Prefecture (Chuxiong) of Yunnan province for providing evidences to chronic disease prevention and control in ethnic minorities. MethodsThe participants of the survey were 6 493 Yi ethnic residents (aged 30 - 79 years) recruited using stratified multistage random cluster sampling in two counties of Chuxiong. Face-to-face interviews with a self-designed questionnaire and physical examination were carried out among the participants from December 2018 through March 2019. The seven characteristics of healthy lifestyle for this study included not smoking currently, never or almost not consuming alcohol, with healthy diet behavior, having relatively high physical exercise, having sufficient sleep, with normal weight, and without central obesity and one score was assigned for each of the characteristics in healthy lifestyle scale. ResultsOf the 6 122 participants completing the survey, 55.8% (3 418) were assessed as with healthy lifestyle based on their healthy lifestyle scores of 4 and above; the mean of healthy lifestyle score was 3.69 ± 1.26 for all the participants and only 0.1% (8) of the participants had the maximum score of 7 for the healthy lifestyle scale. Unconditional multivariate logistic regression analysis revealed that the females (odds ratio [OR] = 2.889, 95% confidence interval [95% CI]: 2.570 - 3.247) and those being married (OR = 1.356, 95% CI: 1.151 - 1.599) are more likely to have a healthy lifestyle compared to the males and those unmarried; while, in comparison to those aged less than 45 years, the participants aged 45 - 59 years (OR = 0.752, 95% CI: 0.654 - 0.865) and ≥ 60 (OR = 0.712, 95% CI: 0.599 - 0.846) are less likely to have a healthy lifestyle. ConclusionThe prevalence of healthy lifestyle is at a low level and affected mainly by gender, age and marital status among 30 - 79 Yi ethnic residents in Chuxiong prefecture.